The effect of global financial crisis on the perfor-mance of Nigerian stock exchange - Ijeoma, Ngozi (International Journal of Accounting and Economics Studies, 2017)
This study assessed the effect of the Global Financial Crisis on the Nigerian Stock market from 2004 to 2013. The objectives of the study include to ascertain the effects of the Global Financial Crisis on the market capitalization of the Nigerian Stock Exchange, to examine the effects of the Global Financial Crisis on the volume and value of shares traded on the floor of the Nigerian Stock Exchange, and to determine the effects of the Global Financial Crisis on the number of listed companies on the Nigerian Stock Exchange. Secondary source of data collection from the Nigerian Stock Exchange was employed. The statistical tools used in this study is the Kruskal-Wallis test. The result of the analysis found that global financial crisis has no significant effect on market capitalization in the Nigerian Stock Exchange. It was equally found that global financial crisis has no significant effect upon the value of shares traded on the floor of the Nigerian Stock Exchange. Findings of the study revealed that there exist no significant relationship between the Global Financial Crisis, and the volume of shares traded on the floor of the Nigerian Stock Exchange. In addition, it was found that there exist no significant relationship between the Global Financial Crisis and number of listed companies in the Nigerian Stock Exchange.